2018
DOI: 10.1177/1455072518778493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of stimulant and depressant pharmacological cognitive enhancement among Norwegian students

Abstract: Aims: To assess the prevalence and factors associated with stimulant and depressant pharmacological cognitive enhancement (PCE) drug use among Norwegian students. Design: In the first wave (T1), 28,553 students were invited to participate, of whom 9370 (32.8%) responded and completed the survey (mean age ¼ 24.9 years, 63.5% female). One year later (T2) those who had responded to some items at T1 were invited to participate in a follow-up survey, where 4783 (47.2%) responded and completed the survey (mean age ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…Similar to some other studies, we found no significant relationships between AoE, extraversion, and extraversion facets (Benotsch et al, 2013;Laakasuo et al, 2018;Middendorff et al, 2012;Sattler & Schunck, 2016). Notably, Myrseth et al (2018) found a negative association between the acceptance of pharmacological enhancement and extraversion, arguing that less extraverted individuals are more likely to enhance themselves to alleviate their characteristic feelings of anxiety and social discomfort.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to some other studies, we found no significant relationships between AoE, extraversion, and extraversion facets (Benotsch et al, 2013;Laakasuo et al, 2018;Middendorff et al, 2012;Sattler & Schunck, 2016). Notably, Myrseth et al (2018) found a negative association between the acceptance of pharmacological enhancement and extraversion, arguing that less extraverted individuals are more likely to enhance themselves to alleviate their characteristic feelings of anxiety and social discomfort.…”
Section: Discussionsupporting
confidence: 87%
“…This explanation is corroborated by another study, which showed that anxious, neurotic individuals preferred anxiety-reducing anti-depressants over performance-enhancing stimulants in exam situations. Hence, neurotic individuals seem to strive for better performance not by enhancing cognitive skills but by regulating emotional distress (Myrseth et al, 2018). However, the current study examined enhancement use in general and without special regards to stress-triggering situations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Stimulants such as Ritalin (methylphenidate) and amphetamine are among the most commonly used drugs in this respect ( 17 ). Among Norwegian higher education students, lifetime use of stimulants as a study drug was reported by 2–4% ( 18 ). Although a temporary increase in memory may be experienced, the use of these drugs is according to a literature review associated with detrimental negative health effects, while not improving learning and school grades ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, internalisation of use is more commonly associated with own use. Another Norwegian study pays attention to a later stage of youth, exploring the prevalence and correlates of cognitive enhancement use of stimulants and depressants among students (Myrseth, Pallesen, Torsheim, & Erevik, 2018). The use of pharmacological cognitive enhancement (PCE) can, according to the authors, be explained by a combination of wanting to improve academic achievement and a general inclination towards substance use.…”
Section: Issue 5 2018mentioning
confidence: 99%